Speedy Grammar: Aplikasi Game untuk Meningkatkan Kemampuan Tata Bahasa Inggris Siswa - Awaliyah Ainun Niswah (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
This study aims to see the improvement of English grammar by students who practice using the Speedy Grammar game application with students who do not use the application, then compare them. This research design is quantitative with an experimental method between two classes, experimental and control class. The subjects of this study were 20 students. As a result, the ability of students who took advantage of the game application increased significantly than students who did not use the application. It can be proven by the value of the pretest and posttest results. During the pretest, the experimental class had a score of 64.70, and the control class had a score of 65.50. Meanwhile, after practicing for 6 times with a duration of 30-50 minutes, the posttest score for the experimental class was 89.60, and the control class was 79.40. Another accurate proof as the answer to the research results of a 2-way (t-tailed) significance value between the two classes shows the number 0.000 on the posttest, so there is a very significant difference. The conclusion again states that the Speedy Grammar game application can be used as a solution to problems when learning English grammar.